Efficacy and toxicity of vemurafenib and cobimetinib in relation to plasma concentrations, after administration via feeding tube in patients with BRAF-mutated thyroid cancer: a case series and review of literature - van Berge Henegouwen, J M; van der Wijngaart, H; Zeverijn, L J; Hoes, L R; Meertens, M; Huitema, A D R; Devriese, L A; Labots, M; Verheul, H M W; Voest, E E; Gelderblom, H (Springer Science and Business Media Deutschland GmbH, 2022)
INTRODUCTION: The combination of vemurafenib, a proto-oncogene B-Raf inhibitor (BRAFi) and cobimetinib, an inhibitor of mitogen-activated protein kinase kinase (MEKi) has shown to improve survival in patients with BRAF V600-mutated melanoma. BRAF mutations are also frequently detected driver mutations in other tumor types, including thyroid carcinoma. Since thyroid carcinoma is not a labeled indication for BRAF/MEKi, a cohort for patients with BRAF V600-mutated thyroid carcinoma was opened within the Drug Rediscovery Protocol (DRUP), a national ongoing pan-cancer multi-drug trial, in which patients receive off-label treatment with approved drugs based on their molecular tumor profile. RESULTS: Here, we present two patients with BRAF-mutated thyroid carcinoma, who were successfully treated with vemurafenib/cobimetinib administered via a feeding tube. Plasma concentrations of vemurafenib and cobimetinib were determined. A partial response was observed in both patients, but they experienced significant toxicity. CONCLUSION: Our cases show that vemurafenib/cobimetinib treatment is effective in BRAF V600-mutated thyroid carcinoma, also when administered via a feeding tube. Although serious side effects occurred in both patients, we hypothesize that this was not attributable to the administration route. Therefore, administration of vemurafenib/cobimetinib by feeding tube is feasible and effective. TRIAL REGISTRATION: Clinical trial identification: NCT02925234.
Keywords: Case series; Cobimetinib; Feeding tube; Plasma concentrations; Thyroid carcinoma; Vemurafenib; Pharmacology (medical); Oncology; Cancer Research; Toxicology; Pharmacology; Journal Article